2010
DOI: 10.1371/journal.pone.0013899
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Three Sampling Methods to Monitor Outcomes of Antiretroviral Treatment Programmes in Low- and Middle-Income Countries

Abstract: BackgroundRetention of patients on antiretroviral therapy (ART) over time is a proxy for quality of care and an outcome indicator to monitor ART programs. Using existing databases (Antiretroviral in Lower Income Countries of the International Databases to Evaluate AIDS and Médecins Sans Frontières), we evaluated three sampling approaches to simplify the generation of outcome indicators.Methods and FindingsWe used individual patient data from 27 ART sites and included 27,201 ART-naive adults (≥15 years) who ini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…A total of 261 papers and 616 conference abstracts were identified by the search strategy and of these 39 studies, 32 papers and 7 conference abstracts, met inclusion criteria[4], [16], [17], [22][24], [27], [31][62] leading to 54 separate cohorts (47 cohorts in 32 papers, and 7 cohorts in 7 abstracts) available for analysis. In 3 papers, data were available for more than one cohort [17], [56], [57] with 2 of these papers reporting on cohorts with and without physical tracing, [17], [57] while the third paper provided data for 2 cohorts that both performed physical tracing [56].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…A total of 261 papers and 616 conference abstracts were identified by the search strategy and of these 39 studies, 32 papers and 7 conference abstracts, met inclusion criteria[4], [16], [17], [22][24], [27], [31][62] leading to 54 separate cohorts (47 cohorts in 32 papers, and 7 cohorts in 7 abstracts) available for analysis. In 3 papers, data were available for more than one cohort [17], [56], [57] with 2 of these papers reporting on cohorts with and without physical tracing, [17], [57] while the third paper provided data for 2 cohorts that both performed physical tracing [56].…”
Section: Resultsmentioning
confidence: 99%
“…In 3 papers, data were available for more than one cohort [17], [56], [57] with 2 of these papers reporting on cohorts with and without physical tracing, [17], [57] while the third paper provided data for 2 cohorts that both performed physical tracing [56]. The 39 included studies reported on 17 countries from sub-Saharan Africa, four multi-country studies from sub-Saharan Africa, three countries from Asia and one from Latin America.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, there is growing concern at the inability of many high-burden countries to report on the outcomes of patients who have been in care for various durations, or even the number of patients in care at a particular point in time [4, 710]. In many instances, countries can only report on the number of patients ever initiated on ART.…”
Section: Introductionmentioning
confidence: 99%